Inflammation and Cardiac Diseases - Feuerstein, Giora Z.; Libby, Peter; Mann, Douglas L. (Birkhäuser Basel, 2003)
Heart failure research is a most active area of research in academic, industrial and government-sponsored research and receives intense clinical attention. The recent recognition that inflammation is a risk factor and prognostic factor for heart disease has laid ground for preventive medicine and even anti-infective strategies in prevention and treatment of heart failure
Keywords: Cardiology